2022
DOI: 10.1002/adma.202206193
|View full text |Cite
|
Sign up to set email alerts
|

Fully Textured, Production‐Line Compatible Monolithic Perovskite/Silicon Tandem Solar Cells Approaching 29% Efficiency

Abstract: Perovskite/silicon tandem solar cells are promising avenues for achieving high‐performance photovoltaics with low costs. However, the highest certified efficiency of perovskite/silicon tandem devices based on economically matured silicon heterojunction technology (SHJ) with fully textured wafer is only 25.2% due to incompatibility between the limitation of fabrication technology which is not compatible with the production‐line silicon wafer. Here, a molecular‐level nanotechnology is developed by designing NiOx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(128 citation statements)
references
References 50 publications
(76 reference statements)
2
112
0
Order By: Relevance
“…It is important to deposit uniform NiO x film with full coverage on the silicon bottom cells by sputtering method for high‐performance tandem solar cells. [ 47 ] We also found that the PCE of Si/PVK tandem device without NiO x is lower due to the poor FF (Figure S10 and Table S4, Supporting Information), which may be attributed to the imperfect contact between Si and PSC. Besides, we also fabricated tandem solar cells based on both PCBM and C 60 , and found that C 60 ‐based tandem devices showed better PCE, as shown in Figure S10, Supporting Information.…”
Section: Resultsmentioning
confidence: 93%
“…It is important to deposit uniform NiO x film with full coverage on the silicon bottom cells by sputtering method for high‐performance tandem solar cells. [ 47 ] We also found that the PCE of Si/PVK tandem device without NiO x is lower due to the poor FF (Figure S10 and Table S4, Supporting Information), which may be attributed to the imperfect contact between Si and PSC. Besides, we also fabricated tandem solar cells based on both PCBM and C 60 , and found that C 60 ‐based tandem devices showed better PCE, as shown in Figure S10, Supporting Information.…”
Section: Resultsmentioning
confidence: 93%
“…With a large market share of more than 90%, low fabrication cost, suitable bandgap, exceptional performance, and life span of over 20 years, Si solar cells are the most mature candidate to combine with PSCs in a tandem device. Indeed, the integration of PSCs with silicon cells to form tandem devices has provided a great opportunity to realize highefficiency PV systems 40,41 . One of the challenges in the development of perovskite/silicon tandem solar cells (PSTSCs) is the requirement for transparent and conductive electrodes to allow for the transmittance of the near-infrared (NIR) part of the incident light through the semitransparent perovskite top subcell to the bottom Si subcell.…”
Section: Tandem Solar Cellsmentioning
confidence: 99%
“…Evaporating a uniform lead halide skeleton followed by solution-processed ammonium salt penetration is a good way to build high-quality perovskite layers. Li et al reported a hybrid vapor-solution deposited p-i-n perovskite top cell on fully textured c-Si solar cell to construct conformal-grown monolithic tandem cells (Figure 3c) [44] . They coevaporated CsBr and PbI 2 on the textured substrate, followed by a spin-coating procedure of a mixture of FABr and FAI with a molar ratio of 1:6.98.…”
Section: Hybrid Vapor-solution Depositionmentioning
confidence: 99%
“…They also demonstrated the large-area scalability of the all-vacuum deposited PSCs with a device structure of ITO/spiro-mF/MAPbI 3 /PC 61 BM/ZnO/Ag. 2,2′, 7,7′ -tetra(N,N-di-tolyl)amino-9,9-spiro-bifluorene (Spiro-TTB) as another spiro-based derivative was also reported for thermal evaporation [44] . Vaynzof and her group obtained a PCE of 16.6% for fully-evaporated Cs 0.1 FA 0.9 PbI 2.9 Br 0.1 PSCs [52] .…”
Section: Thermal Evaporation For Ctlsmentioning
confidence: 99%
See 1 more Smart Citation